Some factors related to lipid profile in obese children at junior high schools in Manado - Anneke Helena Tangkilisan; Kartin Akune (Indonesian Pediatric Society Publishing House, 2007)
Background Factors related to lipid profile in obese children are calorie intake, fast food consuming habit, gender, physical activity, television (TV) watching, sleep duration, and visceral fat distribution. Objective To determine factors related to lipid profile in obese children at junior high school. Methods We studied obese children aged 11-<15 years from November 2004 to February 2005 at junior high school in Manado city. One hundred and seven junior high school children aged 11-<15 years were enrolled in this study, excluding children with acute disease, having hypothyroidism, diabetes mellitus, chronic renal disease, liver disease, and using corticosteroid. The rsik factors considered were calorie intake, fast food consuming habit, gender, physical activity, TV watching, sleep duration, and waist circumference. The outcome measures were total cholesterol, LDL, HDL, non-HDL cholesterol, and triglyceride. Data was analyzed using X 2 , fisher exact test, Spearman's rho and multiple linear regression analysis with stepwise procedure. Results The prevalence of increased total cholesterol was 28%, LDL 44%, triglyceride 16.8%, low HDL cholesterol 6.5%, and non- HDL was 23.3%. There were statistically significant relationship between gender, calorie intake, fast food consuming habit, physical activity, TV watching, sleep duration, and total cholesterol. There were also statistically significant relationship between calorie intake, habit of consuming fast food, physical activity, TV watching, sleep duration, and LDL cholesterol. Fast food consuming habit and TV watching also had statistically significant relationship with HDL cholesterol. There were statistically significant relationship between calorie intake, physical activity, TV watching, and sleep duration with non-HDL cholesterol. Conclusion Duration of TV watching, sleep duration, less physical activity and waist circumference >98 percentile are correlated with hyperlipidemia in obese children.